Barbie Doll Forehead: CAD Design from Silicon Block - Marwah, Shruti; Handa, Arjun (Indian Journal of Plastic Surgery, 2022)
The forehead is an important determinant of masculine or feminine look of the face. There are many methods described to achieve forehead augmentation for a more feminine face, and they include fillers, autologous fat grafting, silicone implant or methyl methacrylate. We present a case of a “Barbie doll forehead,” which is an interesting trend in Asian countries. Availability of silicone implants of various sizes are not uniform and currently unavailable in India. Alternatively, we devised carved silicone block using computer-aided design (CAD). We also discuss the various methods described for forehead augmentation with their advantages and disadvantages.
Keywords: facial feminization; forehead augmentation; silicone implants